Safety and efficacy of azacitidine in Belgian patients with high-risk myelodysplastic syndromes, acute myeloid leukaemia, or chronic myelomonocytic leukaemia: results of a real-life, non-interventional post-marketing survey. Issue 1 (February 2015) - Beguin, Y.; Selleslag, D.; Meers, S.; Graux, C.; Bries, G.; Deeren, D.; Vrelust, I.; Ravoet, C.; Theunissen, K.; Voelter, V.; Potier, H.; Trullemans, F.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: We evaluated azacitidine (Vidaza®) safety and efficacy in patients with myelodysplastic syndrome (MDS), acute myeloid leukaemia (AML), and chronic myelomonocytic leukaemia (CMML), in a real-life setting. Treatment response, dose, and schedule were assessed. Methods: This non-interventional, post-marketing survey included 49/50 patients receiving azacitidine at 14 Belgian haematology centres from 2010–2012. Treatment-emergent adverse events (TEAEs), including treatment-related TEAEs, and serious TEAEs (TESAEs) were recorded throughout the study. Treatment response [complete response (CR), partial response (PR), haematological improvement (HI), stable disease (SD), treatment failure (TF)) and transfusion-independence (TI) were evaluated at completion of a 1-year observation period (1YOP) or at treatment discontinuation, and overall survival (OS), at study conclusion. Results: The median age of patients was 74·7 (range: 43·9–87·8) years; 69·4% had MDS, 26·5% had primary or secondary AML, and 4·1% had CMML. Treatment-related TEAEs, grade 3–4 TEAEs, and TESAEs were reported in 67·3%, 28·6%, and 18·4% of patients, respectively. During 1YOP, patients received a median of 7 (1–12) treatment cycles. Treatment response was assessed for 38/49 patients. Among MDS and CMML patients (n = 29), 41·4% had CR, PR, or HI, 41·4% had SD, and 17·2% had TF. Among AML patients (n = 9), 44·4% had CR or PR, 33·3% had SD, and 22·2% had TF. TI was observed in 14/32 (43·8%) patients who were transfusion-dependent at baseline. Median (95% confidence interval) OS was 490 (326–555) days; 1-year OS estimate was 0·571 (0·422–0·696). Conclusions: Our data support previous findings that azacitidine has a clinically acceptable safety profile and shows efficacy.